Bridging the gaps in detection of structural cardiotoxicity in stem cell-derived cardiomyocytes: promise of miR-133b, miR-184 and miR-208b-3p - Cherubin, M.; Delaunois, A.; Valentin, J. P.; Alaerts, M.; Guns, P. J.; Gryshkova, V. (Frontiers in Pharmacology, 2025)
IntroductionDrug-induced cardiotoxicity is one of the main causes of attrition due to safety in preclinical and clinical development; therefore, identifying novel assays and/or biomarkers to detect potentially harmful candidates is pivotal for the pharmaceutical industry. Over the past decade, microRNAs (miRNAs) have been proposed as alternative translatable biomarkers for cardiotoxicity. Although miRNAs could be useful for detection of cardiotoxicity, they are not routinely assessed in preclinical drug development.MethodsThe current study aimed to investigate dysregulation of miRNAs in human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) and their culture media after exposure to a set of cardiotoxic agents known to cause structural cardiotoxicity by different mechanisms of action. Dose-response analysis of intracellular miRNA expression was conducted after 72-hour incubation with 29 drugs, while the presence of miRNAs in the culture media was evaluated at 24-, 48-, and 72-hour post-treatment in response to 7 selected treatments.ResultsAs a result, we confirmed the upregulation of the following intracellular miRNAs across various drug classes: hsa-miR-96-5p, hsa-miR-126-3p, hsa-miR-133b, hsa-miR-146b-5p, hsa-miR-182-5p, hsa-miR-187-3p and hsa-miR-365a-5p. Interestingly, miRNAs expression in the cell culture media represented different patterns and magnitudes of upregulation, compared to the intracellular miRNAs. hsa-miR-133b, hsa-miRNA-184 and hsa-miR-208b-3p were found to be upregulated the most in the cell culture media.DiscussionThe combination of intracellular and secreted miRNAs in hiPSC-CM might expand the tools for early identification of structural cardiotoxicity in preclinical drug discovery and provide a potential link to circulating miRNAs in patients with drug-induced cardiotoxicity.